Expanding the clinical spectrum of COL2A1 related disorders by a mass like phenotype - Demal, Till Joscha; Scholz, Tasja; Schüler, Helke; Olfe, Jakob; Fröhlich, Anja; Speth, Fabian; Kodolitsch, Yskert von; Mir, Thomas S.; Reichenspurner, Hermann; Kubisch, Christian; Hempel, Maja; Rosenberger, Georg (Scientific reports, 2022)
MASS phenotype is a connective tissue disorder clinically overlapping with Marfan syndrome and caused by pathogenic variants in FBN1. We report four patients from three families presenting with a MASS-like phenotype consisting of tall stature, arachnodactyly, spinal deformations, dural ectasia, pectus and/or feet deformations, osteoarthritis, and/or high arched palate. Gene panel sequencing was negative for FBN1 variants. However, it revealed likely pathogenic missense variants in three individuals [c.3936G > T p.(Lys1312Asn), c.193G > A p.(Asp65Asn)] and a missense variant of unknown significance in the fourth patient [c.4013G > A p.(Ser1338Asn)] in propeptide coding regions of COL2A1. Pathogenic COL2A1 variants are associated with type II collagenopathies comprising a remarkable clinical variablility. Main features include skeletal dysplasia, ocular anomalies, and auditory defects. A MASS-like phenotype has not been associated with COL2A1 variants before. Thus, the identification of likely pathogenic COL2A1 variants in our patients expands the phenotypic spectrum of type II collagenopathies and suggests that a MASS-like phenotype can be assigned to various hereditary disorders of connective tissue. We compare the phenotypes of our patients with related disorders of connective tissue and discuss possible pathomechanisms and genotype-phenotype correlations for the identified COL2A1 variants. Our data recommend COL2A1 sequencing in FBN1-negative patients suggestive for MASS/Marfan-like phenotype (without aortopathy).
Gesehen am 12.05.2022